Analysis of the formation of the problem of independent educational activity in the Ukrainian school and pedagogy (Pedagogy of Higher and Secondary Education, 2021)
The historical and pedagogical analysis of becoming the problem of independent educational activity at Ukrainian school and pedagogics is done in this article. The methodological problems of organization of independent work are considered here.
Keywords: educational activity; independent work; independence; pedagogics; history; creation